Birth weight distribution of Hospital Geral do Grajaú population compared to São Paulo city population - José Ricardo Dias Bertagnon; Jane de Eston Armond; Cintia Leci Rodrigues; Viviane de Almeida Jabur; Gabriela Alba Kuraim; Neil Ferreira Novo; Conceição Aparecida de Matos Segre (Einstein (São Paulo), 2010)
ABSTRACT Objective: To compare the growth curves from a population from a large city suburban hospital with those of the city of São Paulo, São Paulo State, Brazil. Methods: At Hospital Geral do Grajaú, that serves the high pregnancy risk population lacking health facilities, of low education level and smaller number of prenatal visits and great morbidity, a growth curve was built for the newborns, as the Hospital is provided with updated equipment and personnel. The curve was built from the database available containing information on live births during the 2003 to 2007 period and totaling 9,952 newborns, as their weight at birth and gestational age were taken as parameters. The distribution curves of 3%, 10%, 50% and 90% of the Grajaú were compared to those of the city of São Paulo curve. Results: The curves did not significantly differ from those of the São Paulo curve percentiles, as shown by the mean deviation (Z score) calculation, notwithstanding the higher rates for prematurity, low weight, teenager mothers and lack of prenatal visits among the Grajaú population as compared to those of São Paulo. Conclusions: The São Paulo city curve showed to be appropriate for the suburban population despite the existing differences.